The Effect of Leverage, Liquidity, and Profitability on Return on Assets (ROA) at Company X - Hasibuan, Faisal Umardani; Ramadhan, Toto (Westscience Press, 2025)
This study examines the effect of leverage, liquidity, and profitability on Return on Assets (ROA) at Company X using a quantitative research design. Data were collected from 130 samples, analyzed using a Likert scale (1-5), and processed with Structural Equation Modeling-Partial Least Squares (SEM-PLS) 3. The findings reveal that all three variables—leverage, liquidity, and profitability—positively and significantly impact ROA. Liquidity demonstrates the strongest influence, followed by profitability and leverage. The results underscore the importance of liquidity management, operational efficiency, and optimal leverage utilization in enhancing financial performance. These insights provide practical implications for improving the financial strategies of organizations in similar industries.